Beyond Reference Data: A Qualitative Analysis of Nursing Library Chats to Improve Research Health Science Services - Harlow, Samantha (Evidence Based Library and Information Practice, 2021)
Objective - The objective of this study was to analyze trends in academic library reference chat transcripts with nursing themes, in order to improve all library services and resources based on the findings. Methods - In Fall 2018, health science liaison librarians performed a qualitative study by analyzing 60 nursing chat transcripts from LibraryH3lp. These chats were tagged, anonymized, coded, and then analyzed in Atlas TI to identify patterns and trends. Results - Chat analysis showed that librarians staffing chat are meeting the research needs of nursing patrons by helping them find full-text articles and suggesting the appropriate library databases. In order to further improve these virtual services, workshops were offered to Library and Information Science (LIS) interns and staff who answer reference chats. Nursing online tutorials and research guides were also improved based on the results. Conclusion - This study will help academic libraries improve and expand services into the virtual realm, to support library employees and patrons during the COVID-19 pandemic and beyond. Virtual reference chat is not going away; in the current academic environment it is needed more than ever. Using these library chats as the basis for additional chat staff training can reduce staff anxiety and prepare them to better serve patrons.